EFEK INTERVENSI TRAINING DAN COACHING KEBERMAKNAAN KERJA TERHADAP KINERJA KARYAWAN: THE EFFECT OF MEANINGFUL WORK TRAINING AND COACHING INTERVENTION ON EMPLOYEE PERFORMANCE - Eduardo Edwin Ang; Diah Dharmayanti; Deborah C. Widjaja (School of Business, Bogor Agricultural University (SB-IPB), 2020)
This study aims to determine the extent of meaningful work interventions in the form of training and coaching can improve room attendant’s performance (housekeeping department) at Bumi Surabaya City Resort. The research was conducted by the action research method with three stages namely Pre ODI (Diagnosis), ODI (Design and Implementation), and Post ODI (Expected Outcome). ODI itself stands for Organization Development Intervention, which means a structured program designed to solve problems, thereby enabling organizations to achieve goals. Based on Pre ODI results, room attendants have low performance because room attendants do not yet understand the purpose and meaning of their work. Therefore at the ODI stage, researchers provide meaningful work interventions with tools in the form of training and coaching to improve employee performance. To see an improvement in employee performance, the Post ODI researchers conducted a different test (Paired Sample T-Test) before and after the intervention. The results showed that meaningful work training and coaching intervention were able to increase employee performance scores from 3,03 (Pre ODI) to 3,43 (Post ODI). Thus, the research hypothesis can be accepted that there are differences in the average employee performance scores before and after the intervention. Keywords: coaching, employee performance, meaningful work, organization development intervention, training